2011
DOI: 10.2109/jcersj2.119.654
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric properties of (K0.474Na0.474Li0.052)(Nb0.948Sb0.052)O3-Co2O3 lead-free ceramics

Abstract: Lead-free piezoelectric ceramics (K 0.474 addition (0.030.40 mol %) on the phase structure and piezoelectric properties of KNLNS ceramics were systematically studied. The phase structure of KNLNSx%Co 2 O 3 ceramics at room temperature is the coexistence of orthorhombictetragonal phases, and only a small amount of Co 2 O 3 additives can diffuse into KNLNS lattices to form a stable solid solution. The density of ceramics increases gradually with the introduction of Co 2 O 3 . KNLNS0.1 mol %Co 2 O 3 lead-free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…A secondary phase K 3 Li 2 Nb 5 O 15 compound with a tetragonal tungsten bronze structure was detected at x = 0.08; such secondary phase was also recognized in the KNN-LiNbO 3 system. 10) A similar XRPD profile, which implies the formation of an MPB between the orthorhombic and tetragonal phases in the KNNLiSbO 3 system was reported by Wu et al; 16) therefore, it is considered that a MPB region may also be formed in the (1 x)-KNLNSxBLT ceramics. Moreover, the diffraction peaks of the ceramics shift to the higher angles of 2ª with increasing x.…”
Section: Experimental Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…A secondary phase K 3 Li 2 Nb 5 O 15 compound with a tetragonal tungsten bronze structure was detected at x = 0.08; such secondary phase was also recognized in the KNN-LiNbO 3 system. 10) A similar XRPD profile, which implies the formation of an MPB between the orthorhombic and tetragonal phases in the KNNLiSbO 3 system was reported by Wu et al; 16) therefore, it is considered that a MPB region may also be formed in the (1 x)-KNLNSxBLT ceramics. Moreover, the diffraction peaks of the ceramics shift to the higher angles of 2ª with increasing x.…”
Section: Experimental Methodssupporting
confidence: 76%
“…The remanent polarization (P r ) was enhanced from 18.7¯C/cm 2 for x = 0 to 24.3¯C/cm 2 for x = 0.02, although the coercive field (E c ) also increased. Wu et al 16) reported that the increase in E c is related with enhancement of the domain pinning effect, which leads to an increase in the dielectric constant; therefore, substitution of Bi, Li and Ti for K, Na, Li, Nb and Sb may also have an influence on the domain pinning effect. Figure 5 shows the relationship …”
Section: Resultsmentioning
confidence: 99%
“…5b, it can be seen that P r and E c are not maximized at the same composition. This phenomenon has been frequently observed in many material systems (e.g., (Na 1− x K x ) 0.5 Bi 0.5 TiO 3 13, (1– x )K 0.5 Na 0.5 NbO 3 – x LiSbO 3 14, (Ba 0.85 Ca 0.15 )(Ti 1− x Zr x )O 3 15, etc.). This may be attributed to the different dependences of phase structure and grain size on K/Na ratio shown in Figs.…”
Section: Resultssupporting
confidence: 69%
“…Moreover, it is known that such reactions create oxygen vacancies which lead to pinning of domain walls; 17) therefore, they may affect the ferroelectric and piezoelectric properties and the microstructure. Figure 4 shows the P-E hysteresis loops of the KNLNS xmol %Mn 2 O 3 ceramics measured at 50 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…8) 12) It has been reported that high piezoelectric properties are obtained in the KNNLiNbO 3 , KNNLiSbO 3 , and (K,Na)NbO 3 LiTaO 3 LiSbO 3 systems. 13)16) Although charge neutrality of Sb-containing KNN-based ceramics was not maintained by Sb 2 O 3 as the starting material, 13), 17) discussions were based on the Sb 5+ cation. Wu et al reported 17) that the (K 0.474 Na 0.474 Li 0.052 )-(Nb 0.948 Sb 0.052 )O 3 (KNLNS) ceramic, synthesized using Sb 2 O 3 , has a MPB; the addition of Co 2 O 3 was effective in enhancing the dielectric constant at room temperature; therefore, the an effective method to enhance ferroelectric and piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%